Pharmacokinetic Interactions of Phenosanic Acid with Valproic Acid and Carbamazepine in Dogs - M. V. Karlina; V. M. Kosman; V. G. Makarov; M. N. Makarova; S. V. Morozov; E. E. Gushchina; N. V. Zhuravskaya (Безопасность и риск фармакотерапии)
Phenosanic acid prevents convulsions, reduces the frequency of epileptic seizures, and improves cognitive, intellectual and mnestic functions in patients with epilepsy. Therefore, phenosanic acid-based medicinal products are promising candidates for inclusion in combination antiepileptic therapy. In order to combine medicinal products rationally and ensure that the therapy is safe, it is useful to study the pharmacokinetic interaction of medicinal products planned for clinical co-administration.The aim of the study was to examine single-dose pharmacokinetic interactions between Dibufelon® 200 mg capsules (PIQ-PHARMA LLC, Russia) and two medicinal products planned for clinical co-application with it, namely, valproic acid and carbamazepine, in sexually mature dogs.Materials and methods: the study included medicinal products of phenosanic acid (Dibufelon® 200 mg capsules by PIQ-PHARMA LLC, Russia), valproic acid (300 mg prolonged-release film-coated tablets), and carbamazepine (200 mg tablets). The medicinal products were administered to beagle dogs (2 groups of 9 males each) as a single oral dose separately and in the following combinations: phenosanic acid with valproic acid and phenosanic acid with carbamazepine. Dose selection involved adjusting maximum human therapeutic doses using interspecies conversion factors. Phenosanic acid was administered at a dose of 24 mg/kg; valproic acid and carbamazepine were administered at a dose of 60 mg/kg. Blood sampling took place at baseline and in 0.5, 0.75, 1, 2, 4, 6, 8, 10, and 24 h after dosing. Plasma concentrations of active substances were determined by HPLC-UV. Pharmacokinetic interactions were evaluated by changes in the main pharmacokinetic parameters (Сmax, Тmax, AUC0-24, MRT, Т1/2).Results: the study demonstrated rapid gastrointestinal absorption and prolonged systemic circulation of phenosanic acid administered separately (Tmax 2–4 h, T1/2 13–28 h) and combined with valproic acid (Tmax 2 h, T1/2 22 h). When administered with carbamazepine, phenosanic acid was eliminated from the systemic blood flow faster (T1/2 7.4 h).Conclusions: co-administration of phenosanic acid and valproic acid medicinal products had no significant effect on their respective pharmacokinetics. Whereas, the combination of phenosanic acid and carbamazepine demonstrated a significant decrease in the Tmax values of phenosanic acid and the MRT values of carbamazepine. The pharmacokinetic changes suggestive of a possible interaction between phenosanic acid and carbamazepine need further clinical investigation.